Anatomical and Histological Comparative Study of The Proventriculus and Histochmisitry of Mucins in Two Species of Birds Which Differ in Nutrient Nature - Ameer Al-Hamdany; Abdulaziz AL duleemy (College of Education for Pure Sciences, 2019)
The present study aimed to identify the anatomical and histological aspects as well as the histochemistery of mucin of glandular stomach of two birds which differ in their feeding habit. These birds are Sturnus vulgaris and Taenipygia guttat using light microscope and histochemical techniques. The anatomical results showed that the glandular stomach in Taenipygia guttat  was conical or elongated while it was conical shape in the Sturnus vulgaris. Histologically, the result showed that the wall of the glandular stomach in both birds composed  of four layers that comprise the rest of the digestive canal, The mucous layer of the glandular stomach in the two birds consist of folds extending into the glandular stomach cavity which known as mucus folds which is lined by simple epithelial columnar tissue, below it lies the lamina properia which contains superficial glands. While Submucosa is fully occupied with deep gastric glands. Muscularis consist of two layers, The internal circular shape and external longitudinal shape, as well as the serosa covered by mesothelim. Histochemically, the epithelial tissue showed moderate positive response  for PAS reaction  in both birds indicating the presence of moderate quantities of positive mucus materials for PAS reaction For TB technique epithelial tissue showed a positive response in T. guttat indicating that there isrelatively large amounts of acidic mucopolysaccharides in both birds ,while the epithelial tissue in T.guttat. and S.vulgaris showed positive response for AB PH1, AB ph2.5. techniques respectively. AS for AB-PAS epithelial tissue in both birds showed a positive response indicating the presence of neutral and acidic mucins. Superficial gastric glands in both birds showed positive response for all techniques used, as well as the deep gastric glands which showed positive response in T. guttat and  S. vulgaris for PAS techniques, while the AB PH2.5 and  TB technique  showed similar responses in both birds. AS for AB-PAS technique, positive responses as were shown in both birds, indicating large quantities of mucin in the secretions of these glands.